Book review of Shaping the African Savanna by Michael Bollig - M. Timm Hoffman (Pastoralism, 2022)
Book details Bollig, M, Shaping the African Savannah: from Capitalist frontier to Arid Eden in Namibia. Cambridge: Cambridge University Press; 2020. 404 pages, hardback, ISBN 9781108488488